Focal cortical dysplasia imaging discrepancies between MRI and FDG-PET: Unique association with temporal lobe location. (October 2020) - Yokota, Hajime; Uetani, Hiroyuki; Tatekawa, Hiroyuki; Hagiwara, Akifumi; Morimoto, Emiko; Linetsky, Michael; Yoo, Bryan; Ellingson, Benjamin M.; Salamon, Noriko
Highlights: The PET hypometabolic areas were larger than the MRI abnormal areas in 26 patients, whereas were equivalent or smaller than those in 32 patients. Temporal lobe location was found to be a strong predictor of a larger abnormal area on PET than on MRI. The temporal lobe lesions had significantly wider transient zones and lower standardized uptake values than those in the other lobes. Abstract: Purpose: Although magnetic resonance imaging (MRI) and 18 F-2-fluorodeoxyglucose-positron emission tomography (FDG-PET) are used for pre-surgical assessment of focal cortical dysplasia (FCD), they often disagree. This study aimed to identify factors that contribute to discrepancies in FCD imaging between MRI and FDG-PET. Methods: Sixty-two patients (mean age, 18.9 years) with a FCD type I or II were retrospectively selected. These patients were visually categorized into two groups: 1) extent of PET abnormality larger than MRI abnormality and 2) vice versa or equivalent. Predictive factors of these two groups were analyzed by multivariate logistic regression. The extent of hypometabolic transient zone surrounding FCDs and their mean standardized uptake values were measured and compared by the Mann–Whitney U -test. Results: FCDs were detected on MRI and PET in 46 and 55 patients, respectively, whereas no abnormality was detected in 4 patients. The PET hypometabolic areas were larger than the MRI abnormal areas in 26 patients (88 % in the temporal lobe), whereas the PET hypometabolic areas were equivalent or smaller than the MRI abnormal areas in 32 patients (69 % in the frontal lobe). The temporal lobe location was an independent predictor for differentiating the two groups (OR = 35.2, 95 % CI = 6.81–168.0, P < .001). The temporal lobe lesions had significantly wider transient zones and lower standardized uptake values than those in the other lobes ( P < .001, both). Conclusion: The discrepancies between MRI and FDG-PET findings of FCD were associated with temporal lobe location.